1994
DOI: 10.1017/s095927090000280x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting migratory bird routes over the Gulf of Mexico

Abstract: SummaryOver half of the 332 migratory bird species that breed in North America and winter in the tropics are affected by the obstacle to migratory flight presented by the Gulf of Mexico. Landbird migration in the vicinity of the Gulf is considered from an historical perspective, and in light of netting and observational data from the western Gulf coast. A trans-Gulf crossing from the northern Gulf coast to, or over, Yucatan is the most commonly followed fall route for eastern Nearctic migrants that winter in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Further work is needed to determine the factors that have promoted the use of these contrasting strategies by long-distance transoceanic migrants. There is broad evidence that migratory birds time transoceanic departures to coincide with specific meteorological events that provide favourable atmospheric conditions when crossing the Atlantic Ocean [26][27][28][29][30]48] or Gulf of Mexico [49,50]. Therefore, to minimize the energetic costs and risks associated with transoceanic crossings, migrants must identify and respond to the occurrence of specific meteorological events.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to determine the factors that have promoted the use of these contrasting strategies by long-distance transoceanic migrants. There is broad evidence that migratory birds time transoceanic departures to coincide with specific meteorological events that provide favourable atmospheric conditions when crossing the Atlantic Ocean [26][27][28][29][30]48] or Gulf of Mexico [49,50]. Therefore, to minimize the energetic costs and risks associated with transoceanic crossings, migrants must identify and respond to the occurrence of specific meteorological events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is thought that most Blackpoll Warblers (Dendroica striata) fly from the east coast of North America nonstop to South America using favorable winds from fronts early in their journey and trade winds near the end of their trip (Hunt and Eliason 1999, but see Murray 1989, Latta and Brown 1999; these trade winds preclude a similar return trip, necessitating movement to North America and then north. Several studies to date have demonstrated the importance of riparian corridors to migrant birds, particularly in the xeric intermountain West (Rappole and Ramos 1994, Otahal 1995, Winker et al 1997, Yong et al 1998, Finch and Yong 2000. Other studies have shown that migrants concentrate in a variety of inland and upland forests (Petit 2000, Rodewald andBrittingham 2004) and in montane (Austin 1970, Greenberg et al 1974, Blake 1984, Hutto 1985, Carlisle et al 2004) and desert (Wolf et al 1996) habitats, with great variation in abundances among habitats (Hutto 2000).…”
Section: Reviewsmentioning
confidence: 99%
“…In contrast, fall migrant densities in the eastern two sites fall at the lower end of density values for the borderlands region. If, as we have suggested, the eastern sites contain a large proportion of eastern migrants, then perhaps the most likely reason for a pattern of higher densities at Brownsville and Del Rio in spring than fall is that it represents the circular migration pattern described by Rappole and Ramos (1994) in which many eastern migrants that follow a trans-Gulf of Mexico migration route in the fall (passing far east of our study sites and south over the Gulf of Mexico) follow a much more westward trans-and circum-Gulf of Mexico migration route in the spring (coming north overland through Mexico into Texas or crossing the western part of the Gulf of Mexico and making landfall in south Texas). Rappole and Ramos (1994) propose that this circular pattern is caused at least partly by the seasonal weather patterns over the Gulf and their effects on migrants.…”
Section: Geographical and Seasonal Distribution Of Migrant Density -Dmentioning
confidence: 74%